Structural basis of the Axin–adenomatous polyposis coli interaction - Spink, Katharine Eklof (Oxford University Press, 2000)
Axin and the adenomatous polyposis coli (APC) tumor suppressor protein are components of the Wnt/Wingless growth factor signaling pathway. In the absence of Wnt signal, Axin and APC regulate cytoplasmic levels of the proto-oncogene β-catenin through the formation of a large complex containing these three proteins, glycogen synthase kinase 3β (GSK3β) and several other proteins. Both Axin and APC are known to be critical for β-catenin regulation, and truncations in APC that eliminate the Axin-binding site result in human cancers. A protease-resistant domain of Axin that contains the APC-binding site is a member of the regulators of G-protein signaling (RGS) superfamily. The crystal structures of this domain alone and in complex with an Axin-binding sequence from APC reveal that the Axin–APC interaction occurs at a conserved groove on a face of the protein that is distinct from the G-protein interface of classical RGS proteins. The molecular interactions observed in the Axin–APC complex provide a rationale for the evolutionary conservation seen in both proteins.